1999
DOI: 10.1017/s0954579499002151
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal teratogens and the development of adult mental illness

Abstract: Our findings in the Helsinki Influenza Study and the Danish Forty Year Study lead us to conclude that a 2nd-trimester maternal influenza infection may increase risk for adult schizophrenia or adult major affective disorder. More recently we have also reported an increase of unipolar depression among offspring who were exposed prenatally to a severe earthquake (7.8 on the Richter scale) in Tangshan, China. Among the earthquake-exposed males (but not the females), we observed a significantly greater depression r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
121
2
7

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(139 citation statements)
references
References 6 publications
4
121
2
7
Order By: Relevance
“…Lifetime maternal PTSD symptoms have also been shown to dosedependently associate with offspring PTSD symptoms in the general population (Roberts et al, 2012). Comparable findings have been observed in studies of offspring prenatally exposed to nuclear and natural disaster, where offspring of affected parents exhibited greater rates of depression and attention deficit hyperactivity disorder symptoms (Watson et al, 1999;Huizink et al, 2007).…”
Section: Clinical Observations and Significancementioning
confidence: 89%
“…Lifetime maternal PTSD symptoms have also been shown to dosedependently associate with offspring PTSD symptoms in the general population (Roberts et al, 2012). Comparable findings have been observed in studies of offspring prenatally exposed to nuclear and natural disaster, where offspring of affected parents exhibited greater rates of depression and attention deficit hyperactivity disorder symptoms (Watson et al, 1999;Huizink et al, 2007).…”
Section: Clinical Observations and Significancementioning
confidence: 89%
“…In addition, traumatic events not involving abuse, such as parental loss early in life, are associated with developing major depression, anxiety disorders, and schizophrenia in adulthood (Agid et al, 1999;Kendler et al, 1992). Even prenatal stress, because of infection, malnutrition, or maternal psychological stress, is a significant risk factor for developing mental illness in adulthood (Brown et al, 2000(Brown et al, , 2004St Clair et al, 2005;Stein et al, 2009;Watson et al, 1999). In women with major depression, childhood abuse is correlated with smaller hippocampal volume, suggesting long-lasting effects of developmental experience on hippocampal structure in humans (Vythilingam et al, 2002).…”
Section: Effects Of Early-life Experiences On Adult Neurogenesis and mentioning
confidence: 99%
“…It has been reported, for example, that the prevalence of depression was increased in children prenatally exposed to the earthquake in Tangshan, China, in 1976. 156 In rat studies, PS has been reported to result in developmental abnormalities that may have long-term detrimental consequences for brain functioning and may lead to increased susceptibility to psychopathology, including depression, in adulthood. 157,158 Prenatal stressors such as repeated saline injections, daily restraint stress, or crowding (for review see Kofman, 126 Maccari et al 135 ) have been associated with several deficits in the offspring, such as reduced birth weight, increased infant morbidity, locomotor and cognitive retardation, circadian abnormalities and sleep disturbances, alterations in sexual or social behavior, and learning deficits.…”
Section: Stressmentioning
confidence: 99%